Personal and social factors affecting maternal decision-making and breastfeeding practice - Ramos, Rolsanna Rodriguez
Introduction. Breastfeeding can prevent malnutrition, reduce the risk of acute infections, and provide protection against chronic conditions in infants and young children. Comprehending the dynamics and the interactions of the factors that affected the decisions of mothers and their breastfeeding practice may lead nurses to effective interventions that will assist them to be successful in breastfeeding and reach their breastfeeding goals. The aim of this dissertation was to analyze the role of decision-making in breastfeeding and the critical factors for successful practice. It further aimed to validate a hypothesized model of factors leading to successful breastfeeding practice by postpartum mothers. Specifically, this study determined the: 1) influence of personal and social factors on breastfeeding practice a follows: age, number of children, education level, living arrangement, work status, place of residence, and type of delivery on breastfeeding practice; breastfeeding self-efficacy; perceived value to breast milk and breastfeeding; maternal engagement and decision quality; social support; and breastfeeding intention on breastfeeding practice; and 2) influence of breastfeeding self-efficacy, perceived value of breast milk and breastfeeding, maternal engagement and decision quality, social support, and breastfeeding intention on breastfeeding practice. The study also described the process of decision-making of postpartum mothers to breastfeed and how this influenced actual breastfeeding practice. A synthesis of related literature and the expectancy and Contingency Theories and the Theory of Planned Behavior served as a basis for the construction of the variables and the study framework. Methodology. A mixed-method, convergent, parallel design using online or telephone surveys and individual online or telephone interviews. Purposive and referral/snowball sampling was used to recruit postpartum mothers who fulfilled the following eligibility criteria: at least 18 years old Filipino mothers who gave birth to a live term baby within the last 6-12 months and had telephone or internet access. Exclusion criteria included: mothers who (1) had complicated recent delivery. (2) recently delivered an infant with congenital anomaly/ies or malformation/s, (3) had high-risk medical or other conditions that would make breastfeeding difficult during this recent pregnancy, (4) had an infant who died during or after birth in this recent pregnancy, and (5) non-singleton recent pregnancy. Interviews for the qualitative phase of the study were done for a subset of the participants who indicated interest and gave consent to participate. Descriptive and inferential statistics were utilized to analyze the quantitative data. Thematic analysis of qualitative data was done. Results. There were 322 participants who consented to participate in online survey. Majority, 305 (95%), reported positive intention to breastfeed prior to giving birth. Of these 305, although most breastfed their babies (271 mothers, 88.9%). Only 158 mothers 52%) reported doing exclusive breastfeeding and 34 (11%) mothers did not breastfeed at all. Among those who reported negative intention to breastfeed (15, 5%) more than half were still able to practice exclusive breastfeeding (8,53%), 2 (13.3%) breastfed non exclusively and 5 (33%) did not breastfeed at all. Breastfeeding intention was found to have a significant relationship with breastfeeding practice (Fisher’s Exact Test, p-value = 0.02). Mothers had generally high scores on breastfeeding self-efficacy, perceived value, maternal engagement and decision quality, and social support (54.32 土 11.9, 5.29 土 0.72, 37.31 土 9.77, and 6.27 土 0.89, respectively). A significant difference in the mean scores of breastfeeding self-efficacy was found across all levels of breastfeeding practice (H = 79.93, p-value = 0.000). A significant difference existed in the breastfeeding self-efficacy mean scores of those who were non breastfeeding and non exclusively breastfeeding (p = 0.000), those who were non breastfeeding and exclusive breastfeeding (p = 0.000), and exclusively breastfeeding and non exclusively breastfeeding (p = 0.038). A significant difference in the perceived value scores across all levels of breastfeeding practice was also found (H = 26. 48, p-value = 0.000). There is a significant difference in the mean scores of perceived value between non breastfeeding and non exclusive breastfeeding (p=0.000) and non breastfeeding and exclusive breastfeeding (p= 0.000). Multinomial logistic regression analyzes results showed that breastfeeding self efficacy is a significant predictor breastfeeding (Adjusted OR = 1.1 [1.07, 1.13], p = 0.000) and exclusive breastfeeding (Adjusted OR = 1.15 [1.11, 1. 10]. p = 0.000). Being unemployed in a urban area also proved to be significant predictors of breastfeeding (Adjusted OR = 0.45 [0.21, 097], p = 0.04). In the interview with 29 mothers, four themes emerged as a result of the qualitative inquiry: (1) The process of decision-making to breastfeed is different between first time mothers and those with previous experience, (2) Mothers’ breastfeeding decisions are influenced by maternal characteristics and social environment, (3) Breastfeeding practice and duration are influenced by mothers’ personal and social situations, and (4) Mother’s decision to breastfeed and breastfeeding practice were impacted by the COVID-19 pandemic. Conclusions. Work status and place of residence and breastfeeding self-efficacy were found to be predictors of breastfeeding practice. Mothers affirmed the importance of maternal engagement, decision quality, and social support in order to be able to successfully breastfeed. Mother’s involvement in the decision-making process on how to feed her baby was central and crucial factor in breastfeeding initiation and continuation. Being retrospective in nature, self-report bias, self-selection or volunteer bias, social desirability bias, sampling bias, use of online and telephone data gathering methods, and the pandemic situation were the limitations in this study. Recommendation. Prospective studies with larger sample size that could prove causation of factors affecting breastfeeding practice are recommended among mothers with younger infants since 6-12 months postpartum may be too long to get more accurate recall responses, those living in rural areas, those who do not have intention to breastfeed, and who are still pregnant to be able to assess factors that affect their breastfeeding practice to address their concerns early on for more valid conclusions.